Kunstmarkt und Kunstbetrieb in Rom (1750-1850) Akteure und Handlungsorte - Putz, Hannelore; Fronhöfer, Andrea (Bibliothek des Deutschen Historischen Instituts in Rom, 2019)
Between 1750 and 1850, Rome represented a unique crystallization point for the European art market. These conference proceedings examine key players and places and the diverse manifestations of the Roman art market. Discussed topics include local processes of exchange and creative appropriation, negotiations about price and value, and the influence of artists and buyers on the production and reception of visual artworks.